STRATEGI KOMUNIKASI PUBLIC RELATIONS PT CAKRA MAHKOTA DALAM CUSTOMER RELATIONS - Horidatul Bakiyah; Mike Indarsih; Hani Yuniani; Fajar Diah Astuti (Program Studi Ilmu Komunikasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Baturaja, 2022)
PT Cakra Mahkota is one of the companies engaged in Media Communication Services Outside Griya which was founded in 2004 in Jakarta. PT Cakra Mahkota was born in the midst of rapid growth and is developing in the Outside Griya Media industry or better known as Out Of Home Adv (OOH) in Indonesia. With experience in the field of Adv. Print Media more than 10 years. Cakra Mahkota Company provides GRIYA OUTDOOR COMMUNICATION MEDIA SOLUTIONS for industries or companies that will communicate brands, information about products offered according to the target, tailored to the needs of customers in the Dejabodetabek region of Indonesia. PT Cakra Mahkota is a company engaged in services and products. Where the role of PR is hired to build, develop and establish good relations between Customer Relations. The approved product is Bilboard or a service called advertising. While services help customers in receiving advertisements that PT Cakra Mahkota conveyed, a company must establish a harmonious relationship with its customers and company relations. Keywords: Public Relations, PR Strategy. External Public